Kriging algorithm for mapping the gravimetric data in the north of Algeria - Benikhlef, Ilies (Geodetski vestnik, 2024)
The purpose of this work is to analyze and validate the gravimetric information in the study area in order to highlight the valid data for mapping the gravity anomaly from a grid generated by interpolation. In this context, we have performed a first step of data validation using the Kriging interpolation, this method was applied to a set of free-air anomalies reduced by the EGM08 geopotential model, from the test zone located in the north of Algeria, but the data were considered as values of an isotropic variable whose the variographic analysis depends only on the distances between points. In the second step the anisotropic character was taken into account, where the main tasks were to calculate the directional variograms for validating data and to perform interpolation by directional models. Finally, we have performed a computer application for interpolation and validation of gravimetric data by Kriging method, based on the algorithm for validation and grid generation of free-air anomalies, proposed in this article, where the results showed that the free-air anomaly is an isotropic variable which only depends on the distances between positions, and that the values resulting from interpolation are validated by the BGI grid, where the two maps generated one by interpolation and the other by the BGI grid are very similar to confirm the validity of the Kriging algorithm developed in this context.
Keywords: Alžirija; anisotropy; cross-validation; geodezija; gravimetrija; gravimetry; kriging; variogram